Identity Problems from Historical, Cultural and Literary Aspects - Posta, Andrea (Slavica, 2020)
This critique focuses on the latest part of the publication series by the Slavic Historical and Philological Association entitled “Individual and Collective Identities”, which is of great importance for the field of Russian Studies in Hungary as it provides a regular platform for academics with annual conferences. In the three main chapters of the book, identity is approached in different contexts from a historical, cultural, and literary point of view. For this reason, we can say that this collection stands out due to its interdisciplinary nature and complexity serving as a useful resource for those who deal with identity issues.